Sexual Behavior, Desire, and Psychosexual Experience in Gynephilic and Androphilic Trans Women: A Cross-Sectional Multicenter Study - Laube, Jelena S.; Auer, Matthias K.; Biedermann, Sarah V.; Schröder, Johanna; Hildebrandt, Thomas; Nieder, Timo O.; Briken, Peer; Fuss, Johannes (Journal of Sexual Medicine, 2020)
Background: One of the most prominent etiological theories of gender incongruence in trans women proposes a paraphilic erotic target location error (ie, autogynephilia) as a causal factor in gynephilic (ie, exclusively gynephilic and bisexual) trans women. We hypothesized that a paraphilic erotic target location should manifest itself in various aspects of sexual behavior, solitary and dyadic sexual desire, and psychosexual experience. Aim: To compare sexual behavior, sexual desire, and psychosexual experience of exclusively gynephilic and bisexual trans women with that of androphilic trans women to explore whether their sexuality differs substantially. Methods: Trans women diagnosed with gender dysphoria (Diagnostic and Statistical Manual of Mental Disorders–5) were recruited at 4 transgender healthcare centers in Germany. The present study analyzed items on sexual behavior, desire, and experience of a self-report questionnaire, collected as part of a cross-sectional multicenter study. Main Outcomes: Multiple aspects of sexuality were examined using self-constructed items. Sexual desire was measured using the Sexual Desire Inventory and psychosexual experience using the Multidimensional Sexuality Questionnaire. Results: Significantly more exclusively gynephilic than androphilic trans women reported a history of sexual arousal in relation to cross-dressing. However, little evidence was found that gynephilic and androphilic sexual desire, behavior, and psychosexual experience differ profoundly. Interestingly, a statistically non-significant trend indicated that gynephilic trans women who had not yet undergone gender affirming surgery showed the highest levels of sexual desire (solitary and dyadic), whereas the opposite was the case for androphilic trans women. Clinical Translation: Data of this study indicate that sexual orientation does not appear to be a good predicator for sexual behavior, desire, and psychosexual experience in trans women. Strengths and Limitations: We investigated sexual desire and experience using standardized and evaluated measures such as the Sexual Desire Inventory and Multidimensional Sexuality Questionnaire. Future studies with a larger sample size should investigate how different gender affirming medical intervention might have diverging influences on sexual behavior, desire, and experience. Conclusion: Ultimately, this study found little evidence for the hypothesis that sexual behavior, sexual desire, and psychosexual experience differ substantially in gynephilic (exclusively gynephilic and bisexual) and androphilic trans women. Laube JS, Auer M, Biedermann SV, et al. Sexual Behavior, Desire, and Psychosexual Experience in Gynephilic and Androphilic Trans Women: A Cross-Sectional Multicenter Study. J Sex Med 2020;XX:XXX–XXX.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Autogynephilia; Gender Dysphoria; Gender Incongruence; Male To Female; Sexual Orientation; Transgender